Reduction of Target Volume and the Corresponding Dose for the Tumor Regression Field after Induction Chemotherapy in Locoregionally Advanced Nasopharyngeal Carcinoma - Wang, Lei (Cancer Res Treat, 2019)
PURPOSE: This study aims to investigate the feasibility of contouring target volume according to residual tumor and decreasing the dose to the tumor regression field after induction chemotherapy (IC) in locoregionally advanced nasopharyngeal carcinoma (NPC). MATERIALS AND METHODS: From August 2009 to August 2013, patients with stage III–IVB NPC were treated with IC and concurrent chemoradiotherapy. Gross tumor volume of nasopharynx (GTVnx)–residual and gross tumor volume of cervical lymph node (GTVnd)–residual were contoured according to post-IC residual primary tumor and any N+ disease, respectively. The tumor regression field was included in CTVnx1/CTVnd1 and prescribed a dose of 60 Gy. Outcomes and toxicities of all patients were evaluated. RESULTS: A total of 57 patients were enrolled. At a median follow-up of 68 months, three cases displayed locoregional recurrence and one case showed both distant metastasis and locoregional recurrence. All locoregional recurrences were in the GTVnx-residual/GTVnd-residual and in-field. The 5-year overall, locoregional relapse-free, distant metastasis-free, and progression-free survival rates were 82.2%, 87.7%, 85.8% and 80.3%, respectively. CONCLUSION: After IC, contouring of GTVnx-residual/GTVnd-residual as residual tumor volume and distribution 60 Gy ofradiation dose to the tumorregression field may be feasible and need further investigation.